Berkeley’s Best System: An Alternative Approach to Laws of Nature - Walter Ott (Journal of Modern Philosophy)
Contemporary Humeans treat laws of nature as statements of exceptionless regularities that function as the axioms of the best deductive system. Such ‘Best System Accounts’ marry realism about laws with a denial of necessary connections among events. I argue that Hume’s predecessor, George Berkeley, offers a more sophisticated conception of laws, equally consistent with the absence of powers or necessary connections among events in the natural world. On this view, laws are not statements of regularities but the most general rules God follows in producing the world. Pace most commentators, I argue that Berkeley’s view is neither instrumentalist (since law statements have truth values and descriptive content) nor reductionist. More important, the Berkeleyan Best System can solve some of the problems afflicting its Humean rivals, including the problems of theory choice and Nancy Cartwright’s ‘facticity’ dilemma. Some of these solutions are available in the contemporary context, without any appeal to God. Berkeley’s account deserves to be taken seriously in its own right.